Exploring The Interplay Between Interpersonal Communication Skills, Perceived Stress, And Coping Strategies In Early Adulthood: A Mixed-Methods Approach - Mohamad Alppy Valdez; Ferry Darmawan; Roswiyani Roswiyani (Jurnal Edusci, 2026)
Background. Early adulthood is marked by increasing academic and interpersonal demands that heighten vulnerability to stress. Interpersonal communication is considered a key psychosocial resource, yet its role in stress regulation among university students remains underexplored. Methods. This mixed-methods study examined the relationship between interpersonal communication skills and perceived stress among 114 university students. Quantitative analyses included Pearson correlation, simple linear regression, and group comparisons, while qualitative data from open-ended responses were analyzed thematically using Lazarus and Folkman’s transactional model of stress and coping. Result. The results showed a significant negative correlation between overall interpersonal communication skills and perceived stress (r = −.185, p = .025). Regression analysis confirmed interpersonal communication skills as a significant negative predictor of perceived stress (β = −.185, p = .049), explaining 3.4% of the variance. No significant relationships were found between perceived stress and individual communication dimensions. Female students reported higher perceived stress than male students, whereas no differences were observed in interpersonal communication skills. Perceived stress and communication skills also did not differ by religion, education level, or ethnic background. Conclusion. Qualitative findings revealed that stress was experienced as a multidimensional and cumulative process, shaped by academic pressure, interpersonal conflict, family issues, environmental conditions, physical health, and intrapersonal struggles. Participants reported using a combination of adaptive and maladaptive coping strategies. Implementation. These findings suggest that interpersonal communication operates as a holistic protective resource rather than through isolated skill components. By integrating quantitative and qualitative evidence, this study extends existing research by highlighting the contextual and multifaceted nature of stress and coping in early adulthood.